PENGARUH REWARD DAN PUNISHMENT SEBAGAI SKEMA HASIL EVALUASI KINERJA KARYAWAN PADA PERUSAHAAN SWASTA - Geta Ambartiasari (Al Mashaadir : Jurnal Ilmu Syariah, 2020)
The issue at this writing is about the results of the evaluation was run by a company after they to be the best company since last two years, it was interesting to discuss how evaluation result conducted on reward and punishment. The desire to know about how to stimulate employee performance with these two methods is worth executing. So it found the implementation of the reward is better to run than the punishment, but the reward and punishment should be run together. When running the punishment company need to give gradual warning to employee, because the purposes of reward and punishment are to increase employee performances. The research method used in this journal descriptive qualitative research with subject and object of this research is an employee at sales executive position and supported by observations from data collected.